Effective faraid system using rule-based - Harini Harani (2019)
Faraid cases in Malaysia often occur due to the lack of knowledge about Faraid, especially for heirs who want to calculate Faraid, because Faraid is based on the Qur'an and Hadith. Faraid is one of the ways to distribute inheritance to surviving beneficiaries and depends on the prescribed conditions. It requires some conditions for division of the property. These requirements are very important to determine the amount of money the surviving beneficiaries will receive. It seems this problem need to be solved because the heirs will face some difficulties such as knowledge, time and energy consuming to make calculations of faraid. Besides, we lack of expertise in F araid fields and the calculated data will not be saved, if the same thing repeats, Faraid calculations need to be restarted. The proposed of Effective Faraid system is will help users to calculate about Faraid and informs the eligible beneficiary and Faraid division according to the prescribed conditions such as amount of estate, number of heirs, condition for heirs and others. The result is this system will display the results that users have set the conditions set. Users can also chat with the admin and ask about Faraid's knowledge through this system. The user scope for this system is for public user and admin. Public user can access the system when they have register or login as a member. In addition, to accomplish this system,appropriate data must be entered into the system. In terms of efficiency, vanous algorithms are able to accomplish operations or problem solving easily and quickly. In this system Rule Based technique will be used as way to store and manipulate knowledge to interpret information in a useful way. For conclusion, Effective Faraid System will help a user to solve the faraid problem and also can know basic of Faraid's knowledge. In addition, it can help the public to know faraid more closely.